Candidate Selection in Germany: Local and Regional Party Elites Still in Control?. (June 2016) - Detterbeck, Klaus
In comparative terms, the strong legal regulation of internal party processes is a specific feature of the German party democracy. Local and regional party conventions are the formal sites of decision making in selecting parliamentary candidates. The national party level is relatively excluded from the procedures. The article argues that the decentralization of intraparty competences has facilitated a gatekeeping role for local and regional party elites. At the constituency level, most often a single candidate is presented to the party convention after he or she has been appointed in the informal preselection activities of local party elites. Gaining a local nomination is the crucial step for obtaining a federal parliamentary mandate, either by winning a direct constituency mandate or being awarded a safe list position. At the regional level, Land party elites are in control of producing balanced party lists. The article also looks at newer developments, such as the introduction of party primaries and gender quotas. It shows that these developments have somehow weakened, but not fundamentally altered, the predominance of subnational party elites in candidate selection.